Profiles of Long Non-Coding RNAs and mRNA Expression in Human Macrophages Regulated by Interleukin-27 - Hu, Xiaojun (Int J Mol Sci, 2019)
Macrophages play an essential role in the immune system. Recent studies have shown that long non-coding RNAs (lncRNAs) can regulate genes encoding products involved in the immune response. Interleukin (IL)-27 is a member of the IL-6/IL-12 family of cytokines with broad anti-viral effects that inhibits human immunodeficiency virus (HIV) type-1 and herpes simplex virus (HSV). However, little is known about the role of lncRNAs in macrophages affected by IL-27. Therefore, we investigated the expression profiles of mRNA and lncRNA in human monocyte-derived macrophages (MDMs) regulated by IL-27. Monocytes were differentiated in the presence of macrophage-colony stimulatory factor (M-CSF)- or human AB serum with or without IL-27, and these cells were the subject for the profile analysis using RNA-Seq. We identified 146 lncRNAs (including 88 novel ones) and 434 coding genes were differentially regulated by IL-27 in both M-CSF- and AB serum-induced macrophages. Using weighted gene co-expression network analysis, we obtained four modules. The immune system, cell cycle, and regulation of complement cascade pathways were enriched in different modules. The network of mRNAs and lncRNAs in the pathways suggest that lncRNAs might regulate immune activity in macrophages. This study provides potential insight into the roles of lncRNA in macrophages regulated by IL-27.